2023
DOI: 10.3389/fmed.2023.1127529
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Tissue positivity for SARS-CoV-2 in a preterm born infant death of thrombosis: possible intrauterine transmission

Abstract: Intrauterine transmission of SARS-CoV-2 (Severe Acute Respiratory Syndrome Corona Virus 2) is still matter of debate among scientists and there is limited information concerning this aspect of research. This could lead to severe complications of the growing fetus and, theoretically, of the newborn as well. We report the case of a male infant of 1,100 grams, born at 27th week of gestation to a SARS-CoV-2 mother, tested negative for viral detection at delivery. He was immediately admitted to neonatal Intensive C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…29 Recently, a case of newborn thrombo-embolism presents strong evidence of intrauterine transmission of SARS-CoV-2. 30 SARS-CoV-2 N-protein and Spike RBD were detected particularly in the esophagus, stomach, spleen, and heart, with a significantly higher H-Score than the placenta, suggesting a possible intrauterine transmission.…”
Section: Intrauterine Transmissionmentioning
confidence: 94%
See 1 more Smart Citation
“…29 Recently, a case of newborn thrombo-embolism presents strong evidence of intrauterine transmission of SARS-CoV-2. 30 SARS-CoV-2 N-protein and Spike RBD were detected particularly in the esophagus, stomach, spleen, and heart, with a significantly higher H-Score than the placenta, suggesting a possible intrauterine transmission.…”
Section: Intrauterine Transmissionmentioning
confidence: 94%
“…Even IgM is not transferred transplacentally in healthy pregnant women, it can be transferred through mother‐to‐child in severe inflammation of the birth canal or presence of viral cytotoxic effects 29 . Recently, a case of newborn thrombo‐embolism presents strong evidence of intrauterine transmission of SARS‐CoV‐2 30 . SARS‐CoV‐2 N‐protein and Spike RBD were detected particularly in the esophagus, stomach, spleen, and heart, with a significantly higher H‐Score than the placenta, suggesting a possible intrauterine transmission.…”
Section: Potential Vertical Transmission Of Sars‐cov‐2mentioning
confidence: 99%
“…However, a recent study reported a case of a 34-year-old woman admitted to the ICU due to severe COVID-19 infection whose newborn died by pulmonary embolism and thrombosis of the superior vena cava, in which immunohistochemical analysis demonstrated a SARS-CoV-2 NP presence in neonatal tissues [ 274 ].…”
Section: Emerging Viruses and Pregnancymentioning
confidence: 99%